2020
DOI: 10.14740/wjnu398
|View full text |Cite
|
Sign up to set email alerts
|

Are Inflammatory Markers Useful in Predicting Urinary Tract Infection After Transrectal Ultrasound-Guided Biopsy of the Prostate?

Abstract: Background: Sepsis is a serious and life-threatening complication after transrectal ultrasound (TRUS)-guided prostate biopsy. It is critical to predict its occurrence prior to conducting the biopsy. The neutrophil/lymphocyte ratio (NLR) and platelet/lymphocyte (PLR) have been proven to be promising diagnostic indicators of infectious complications after various surgical procedures. The aim of this study was to determine whether inflammatory markers, NLR and PLR ratios, are useful surrogates to predict sepsis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Heidar et al reviewed the total number of 378 patients who underwent in case of TRUS biopsy, among them 31 developed sepsis. They did not find the links between the pre-biopsy NLR or PLR and the development of sepsis post-biopsy, moreover the statistically remarkable correlation between the sepsis and pre-biopsy urine analysis as well as prostate-specific antigen level (PSA) [18]. Kazimoglu et al reported a significant decrease of NLR after renal transplantation and an important variation in the NLR was noted in between the Escherichia coli (E. coli) infected and uninfected recipients [19].…”
Section: Nlr and Plr In Urinary Tract Infectionmentioning
confidence: 99%
“…Heidar et al reviewed the total number of 378 patients who underwent in case of TRUS biopsy, among them 31 developed sepsis. They did not find the links between the pre-biopsy NLR or PLR and the development of sepsis post-biopsy, moreover the statistically remarkable correlation between the sepsis and pre-biopsy urine analysis as well as prostate-specific antigen level (PSA) [18]. Kazimoglu et al reported a significant decrease of NLR after renal transplantation and an important variation in the NLR was noted in between the Escherichia coli (E. coli) infected and uninfected recipients [19].…”
Section: Nlr and Plr In Urinary Tract Infectionmentioning
confidence: 99%